Marine climate variability based on weather patterns for a complicated island setting: The New Zealand case. (22nd November 2018) - Rueda, Ana; Cagigal, Laura; Antolínez, Jose A. A.; Albuquerque, Joao C.; Castanedo, Sonia; Coco, Giovanni; Méndez, Fernando J.
Abstract : Understanding marine climate variability is important for coastal planning and marine operations. It is also particularly challenging for complicated settings (e.g., islands) and data‐poor regions. The aim of this work is to establish a relationship between daily synoptic atmospheric patterns, and wave and storm surge conditions around New Zealand waters, based on instrumental and reanalysis data. The daily predictor we developed is able to represent sea and swell wave conditions as well as storm surge variability over different temporal scales. However, when climate variability is analysed on a longer temporal period, based on the 20th century reanalysis, large inhomogeneities are found. This highlights the dangers related to assessing climate variability, especially in data‐poor regions (such as New Zealand), where inhomogeneities could be interpreted as actual changes. Abstract : This work is conceived to present a general methodology to relate atmospheric conditions to regional wave and water level variables, which are drivers of coastal change. The established relationship allows to explore climate variability at different temporal scales. Our approach is general and leads to a relationship between waves and water levels with atmospheric conditions, which is envisaged to be a useful tool for the broad scientific community studying coastal changes.